Procurement application solutions in cloud environment, evolution and trends - Štangl, Rastislav (2013)
The goal of the presented thesis is to screen market and to assess the Procurement application solutions provided in cloud with focus on SMB companies. Understanding of Procurement process is base for identification of key functions and requirements on Procurement applications. Market research results in initial high level picture about the Procurement applications available with attention to cloud. Procurement applications assessment determines conclusions on market evolution and trends. The first part of the thesis introduces theoretical background of Procurement process and cloud computing. This part is completed by the list of key functions and requirements, of expected benefits, and of the steps that are important during assessment and selection of Procurement application in business. The second part investigates the Procurement application market and vendors. The screening is oriented on application features, client set, delivery models, and on other characteristics. Eight Procurement application solutions were selected for detailed assessment: Bellwether ePMX, Compleat Spend Control, Coupa, eBid eXchange, Ion Wave Technologies, PurchaseControl, Trade Interchange (ARCUS), and Xtenza. Assessment of the applications results in comparative data that are presented in predefined structure. The primary focus is on application features and Procurement functions supported. Other important evaluation categories are delivery models, security, underlying infrastructure, approval workflows, and commercials. Communication with application vendors contributed to the assessment. This part is finalized with evolution and trend conclusions focusing on cloud proliferation dynamics, and on forecast of new application functions and features that will result in new business benefits.